BlackGEM: the wide-field multi-band optical telescope array - Groot, Paul J.; Bloemen, Steven; Vreeswijk, Paul M.; Jonker, Peter G.; Pieterse, Danielle; Engels, Arno; Michiels, Jeroen; Bakker, Roy; Hahn, Floris; Raskin, Gert; Morren, Johan; Navarro, Ramon; et al. (SPIE, 2022)
The BlackGEM array Phase I consists of three wide field, optical telescopes, located at the ESO La Silla Observatory, Chile. Each telescope is of a modified Dall-Kirkham design, using an 0.6m primary mirror and a 110 Mpix STA1600 CCD to give a 2.7 square degrees field-of-view sampled at 0.56"/pixel. Preliminary commissioning data shows performance on-par with design specifications. Data obtained with the BlackGEM prototype MeerLICHT highlights the capabilities of the design with a 5-sigma limiting magnitude of mAB=22.2 in 300s of integration under dark-sky conditions. Extrapolation to the 1" seeing-conditions expected at La Silla shows that the main goal of BlackGEM to probe down to mAB=23 in 300s can be met. The project suffered a 2-year COVID-19 delay. Commissioning of the array has currently been resumed and science operations are expected to start in Q3/Q4 of 2022. The science programs include the follow-up of gravitational wave alerts from LIGO/Virgo/KAGRA, a six-filter Southern Sky Survey, a Fast Synoptic Survey on selected fields, a Local Universe intra-night monitoring program and a inter-night single-band monitoring for slower transients.